Antibacterial Effect of Aqueous and Alcoholic Propolis Extracts on Aggregatibacter Actinomycetemcomitans in Patients with Chronic Periodontitis (An In-vitro Study) - Saba S Mahdi; Liqaa M Ibrahim; Wifaq M Ali (College of Dentistry/ University of Baghdad, 2015)
Background: Propolis has received great interest because of its wide range antimicrobial activity. Propolis also called (bee glue) due to its collection by (Apismellifera) honeybees from various plants resinous substance. The aim of this study was to determine the antibacterial effect of propolis extracts (aqueous and alcoholic) on anaerobic periodontal pathogen namely Aggregatibacteractinomycetemcomitans. Materials and Methods: Strains of Aggregatibacter actinomycetemcomitans wasisolated from pockets of systemically healthy patients aged between 35-55 years old suffering from chronic periodontitis with pocket depths of 5-6 mm, the bacteria cultured on special blood Agar plates solid media. Propolis was extracted by using water and alcohol. Agar well technique was used to study the sensitivity of Aggregatibacter actinomycetemcomitans to different concentrations of propolis extracts (70, 80, 90, 100, 125 and 150) mg/mland other control agents (distilled water and chlorhexidine 0.2%). Results: Aggregatibacter actinomycetemcomitans was sensitive to propolis extracts; alcoholic extract was more effective than aqueous extract.All concentrations of propolis extracts showed smaller inhibition zones than 0,2% CHX except 150 mg/ml concentration of aqueous extract ,(100, 125 and 150)mg/ml concentrations of alcoholic extract showed larger inhibition zones than 0,2% CHX. Conclusion: Propolis extracts were effective against anaerobic periodontal pathogens (Aggregatibacter actinomycetemcomitans).